Sharia Banking Support to Help IT Start-Up Development in Bina Nusantara University - Prakosa, Gatot Hendro; Permana, Erwin; Hartanto, Hartanto; Pramudito, Onggo (Bina Nusantara University, 2017)
Â This research was to find the possibilities of using the sharia banking method as the funding source alternatives for students or graduated students of IT start-up in Bina Nusantara University. This research was a qualitative research. In-depth Interview method was used to get the information. The researchers interviewed several informants that were considered as the competence individuals in Sharia Banking. It is found that sharia Banks are using the fatwa of Dewan Syariah Nasional (DSN - National Sharia Council) as their operational reference, that is included the fatwa on business funding. All informants agree that IT start-up has not been discussed by the DSN, and there is no any fatwa about it. However, IT start-up has been considered as the kind of business that cannot be funded by sharia banks due to the method of the business itself, which can be considered as gharar (a business that isforbidden in Islam).